A procedure for interaction between rock mass and liner for deep circular tunnel based on new solution of longitudinal displacement profile. Issue 1 (2nd January 2022) - Shen, Qiang; Zheng, Jun-Jie; Cui, Lan; Pan, Yu; Cui, Bo
Abstract: A new solution for the longitudinal displacement profile (LDP) is proposed based on three-dimensional finite-difference method. The improved convergence-confinement method (CCM) is divided into two stages. In the first stage, the fictitious support pressure can be derived, representing the support pressure acting on the periphery of the tunnel by the rock mass itself. In the second stage, the fictitious support pressure transforms to the pressure on liner, and this progress reflects the interaction between rock mass and liner. According to two-stage analysis, a computing procedure is proposed for calculating pressure and deformation of rock and liner. By comparing with the results of other approaches, the procedure is proved to be correct. The influences of elasticity modulus, thickness of liner, and supporting time are discussed individually. The results indicate that the final pressure on liner can be reduced by reducing stiffness of liner and postponing supporting time. To prevent the liner from yielding, the prior measure is to postpone supporting time, and meanwhile, the liner with lower elasticity modulus and smaller thickness can be selected. In final, a practical example is performed by utilising this procedure, confirming it can provide reference to tunnel engineering design.